Thanksgiving for Emily Ann - Johnston, Teresa; Newton, Vanessa (New York : Cartwheel Books, 2014)
Emily Ann learns about the meaning of Thanksgiving when her family gathers around the dinner table.
Keywords: Thanksgiving Day -- Juvenile fiction; Gratitude -- Juvenile fiction; Families -- Juvenile fiction; Stories in rhyme; Stories in rhyme; Thanksgiving Day -- Fiction; Gratitude -- Fiction; Family life -- Fiction